Penguatan Sumber Daya Insani Menuju Unit Usaha Berkualitas Di Koperasi Rakhis PP. Nazhatut Thullab Sampang - Maryam Qadarin; Mahmudi; Suliyeh; Siska Aprilia; Sahrul (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2024)
Business unit management, especially in cooperatives, plays a central role in the economic growth of communities. A study was conducted on Rakhis Cooperative in PP. Nazhatut Thullab, Prajjan Village, Camplong Subdistrict, Sampang Regency, identifying challenges, particularly related to human resources quality. The analysis reveals variations in employees' education and the need to enhance technical skills, understanding of cooperative regulations, and mastery of information technology. Therefore, community service activities focus on skills training, emphasizing financial management, marketing, and information technology. The method involves needs analysis, training program design, active participant involvement, selection of quality speakers, ongoing monitoring and evaluation, and dissemination of results. The results show the success of training in improving employees' knowledge and skills. Despite facing some obstacles, such as resistance to change, development opportunities include advanced programs and partnerships with relevant institutions or experts. In conclusion, strengthening human resources in Rakhis Cooperative through training can be a key to sustainability and a more significant contribution to economic and social development in the region